Type-A response regulators negatively mediate heat stress response by altering redox homeostasis in Arabidopsis - Jindal, Sunita; Kerchev, Pavel; Berka, Miroslav; Černý, Martin; Botta, Halidev Krishna; Laxmi, Ashverya; Brzobohatý, Břetislav (Frontiers in Plant Science, 2022)
Besides the long-standing role of cytokinins (CKs) as growth regulators, their current positioning at the interface of development and stress responses is coming into recognition. The current evidence suggests the notion that CKs are involved in heat stress response (HSR), however, the role of CK signaling components is still elusive. In this study, we have identified a role of the CK signaling components type-A Arabidopsis response regulators (ARRs) in heat stress response in Arabidopsis. The mutants lacking multiple type-A ARR genes exhibit improved basal and acquired thermotolerance and, altered response to oxidative stress in our physiological analyses. Through proteomics profiling we show that the type-A arr mutants experience a ‘stress-primed’ state enabling them to respond more efficiently upon exposure to real stress stimuli. A substantial number of proteins that are involved in the heat-acclimatization process such as the proteins related to cellular redox status and heat shock, are already altered in the type-A arr mutants without a prior exposure to stress conditions. The metabolomics analyses further reveal that the mutants accumulate higher amounts of α-and γ-tocopherols, which are important antioxidants for protection against oxidative damage. Collectively, our results suggest that the type-A ARRs play an important role in heat stress response by affecting the redox homeostasis in Arabidopsis.